2010
DOI: 10.1073/pnas.1008930107
|View full text |Cite
|
Sign up to set email alerts
|

D-peptide inhibitors of the p53–MDM2 interaction for targeted molecular therapy of malignant neoplasms

Abstract: The oncoproteins MDM2 and MDMX negatively regulate the activity and stability of the tumor suppressor protein p53, conferring tumor development and survival. Antagonists targeting the p53-binding domains of MDM2 and MDMX kill tumor cells both in vitro and in vivo by reactivating the p53 pathway, promising a class of antitumor agents for cancer therapy. Aided by native chemical ligation and mirror image phage display, we recently identified a D-peptide inhibitor of the p53-MDM2 interaction termed The tumor sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
145
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(159 citation statements)
references
References 56 publications
14
145
0
Order By: Relevance
“…"Mirror-image phage display," a powerful method pioneered by Kim and co-workers, has identified D peptides that bind tightly to L proteins (6). A few of these heterochiral complexes have been characterized at atomic resolution (7,8), but no general principles of heterochiral recognition have emerged. Shai and co-workers have reported that D peptides corresponding to transmembrane helices of several integral membrane proteins can pair with the natural L-peptide helix within a lipid bilayer (9-11).…”
mentioning
confidence: 99%
“…"Mirror-image phage display," a powerful method pioneered by Kim and co-workers, has identified D peptides that bind tightly to L proteins (6). A few of these heterochiral complexes have been characterized at atomic resolution (7,8), but no general principles of heterochiral recognition have emerged. Shai and co-workers have reported that D peptides corresponding to transmembrane helices of several integral membrane proteins can pair with the natural L-peptide helix within a lipid bilayer (9-11).…”
mentioning
confidence: 99%
“…Such D-peptide ligands would be resistant to proteolytic digestion in vivo, and for that reason they have excited a great deal of interest. Although mirror image phage display has been used in a number of academic studies (12)(13)(14), it has not yet led to the development of D-peptides as therapeutics.…”
mentioning
confidence: 99%
“…Although most therapeutic peptides are directed toward extracellular targets (38), the increasing use of cell-penetrating peptide sequences to transport "cargo," including peptide therapeutics, across the cell membrane has opened the door to many intracellular targets, including many proteins implicated in cancer (39,40). Recently, small peptides have shown efficacy in blocking the interaction of Bcl-XL with Bax (34) and of p53 with MDM2 (36) in preclinical cancer therapy models. At present, we have no indication that the use of Disruptin would be therapeutically viable, either alone or by potentiating the effects of radiation or chemotherapy.…”
Section: Discussionmentioning
confidence: 99%